2010
DOI: 10.4088/pcc.10m00958blu
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Premedical Undergraduates

Abstract: These findings underscore the importance of understanding the unique strains and mental health consequences of a premedical curriculum, especially for women and certain minority ethnic populations. A meaningful next step would be a larger study, conducted by several representative university campuses, to confirm these findings; a follow-up of these cohorts could track longitudinal progress. More research must be done to determine the etiology of these findings with the ultimate intention of identifying opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
18
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 0 publications
1
18
0
4
Order By: Relevance
“…Several studies do not find the relationship 1,15 while other studies show significant association between the two variables. 26,29 For example, Fang et al 29 suggests that female students are more vulnerable to certain stress and thus more prone to suffer from stress-related depression. This is similar to another study, which involved pharmacy students.…”
mentioning
confidence: 99%
“…Several studies do not find the relationship 1,15 while other studies show significant association between the two variables. 26,29 For example, Fang et al 29 suggests that female students are more vulnerable to certain stress and thus more prone to suffer from stress-related depression. This is similar to another study, which involved pharmacy students.…”
mentioning
confidence: 99%
“…It is concluded that experiences in the university may hinder adaptation, good academic performance (Hussain et al, 2013;Ramírez et al, 2009;Shamsuddin et al, 2013;Wristen, 2013) and effect the mental health of the student (Baptista et al, 2012;Bitsika & Sharpley, 2012;Fang et al, 2010;Gonçalves et al, 2012;Osada et al, 2010). Conversely, social skills can promote mental health (Adlaf et al, 2001;Bolsoni-Silva & Loureiro, 2014;Bolsoni-Silva & Loureiro, 2015a), adaptation (Monteiro et al, 2008), academic performance (López-Bárcena et al, 2009) and remaining in the university.…”
Section: Discussionmentioning
confidence: 99%
“…The school characteristic, the year of the student in the university, also seems to influence the social skills repertoire (Bolsoni-Silva et al, 2010) and mental health problems. It has been highlighted that mental disorders are more frequent in the first academic year (Bolsoni-Silva & Loureiro, 2015b, Fang et al, 2010, Adlaf et al, 2001, although Shamsuddin et al (2013), with older students of earlier years generally presenting more indicators of anxiety and depression. Another school characteristic associated with mental health problems concerns the area of the course, which has been addressed in the studies of Cerchiari et al (2005), Neves and Dalgalarrondo (2007) and Bolsoni-Silva and Loureiro (2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies described women as being particularly at risk of developing higher levels of mental distress before and during the dissection course (Hancock et al,2004; Boeckers et al,2010). Anatomists should get to know more about the ethnic minorities they teach, as these were also found to have a greater prevalence of depression (Fang et al,2010), and anatomy teachers might be less familiar with their understanding of death and dying. Future studies might also focus on an objectivation of these data by implementing validated instruments like the “Brief Symptom Inventory” (Franke,2000), “Medical Student Stress Profile” (MSSP) (O'Rourke et al,2010), the newly developed by Dyrbye et al (2010) “Medical Student Well‐Being Index” (MSWBI), or by obtaining biological samples from students to assess stress and its effects on the immune system (Lester et al,2010).…”
Section: Discussionmentioning
confidence: 99%